Plastic rubber and vulcanization molding process thereof

CN122914408APending Publication Date: 2026-10-16WUHAN RUIZHIYUAN PLASTIC IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611314539.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

随着汽车、装备制造、油封密封和减震部件等领域对尺寸稳定性、耐油性、耐压缩永久变形和批次一致性的要求提高,传统以未改性天然橡胶直接与塑料共混、普通硫磺单一硫化体系、一次性混炼及恒温硫化为主的工艺,虽然能够满足部分常规低端制品的生产需求,但在向中高端制品升级时,逐渐暴露出界面相容性不足、填料分散不稳定、交联反应难以精细调控以及成型缺陷较多等问题,难以稳定满足中高端橡塑制品的量产标准

Benefits of technology

本发明先采用甲基丙烯酸缩水甘油酯搭配聚醚胺复配改性天然橡胶,在橡胶分子链引入极性活性基团,大幅提升天然橡胶与高密度聚乙烯之间的界面亲和能力;同时通过正十二烷基膦酸与脂肪醇聚氧乙烯醚AEO-9协同螯合包覆气相二氧化硅、凹凸棒石复配填料,并通过马来酸酐接枝三元乙丙橡胶预溶胶液进行热定型包覆,完成无机填料表面有机化修饰,降低填料表面活化能,避免填料在橡塑基体中发生团聚。改性橡胶与改性填料双重协同作用,消除橡塑共混体系相分离、分层缺陷,成品内部结构均匀稳定,从根源解决传统工艺制品力学性能波动大、生产良品率低的行业痛点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122914408A_ABST
    Figure CN122914408A_ABST
Patent Text Reader

Abstract

The application discloses a vulcanization forming process of plastic rubber and relates to the technical field of high polymer materials.The process is characterized in that firstly, natural raw rubber is opened and mixed into thin passages, and then the natural rubber is modified by glycidyl methacrylate and polyether amine synergistic grafting; secondly, fumed silica and attapulgite clay are compounded, and then the compound is coated by chelation and matched with maleic anhydride grafted EPDM rubber to obtain a composite functional filler; thirdly, the rubber-plastic matrix, the filler and the two-component vulcanization system are differentially mixed in three stages; finally, the rubber is vulcanized and formed by adopting a constant pressure gradient after standing and curing. The application can improve the compatibility of the rubber-plastic interface, avoid filler aggregation and phase separation, accurately control the crosslinking reaction, release internal stress in steps and fully exhaust air; the obtained plastic rubber has a uniform internal structure, excellent mechanical properties, compression deformation resistance and oil resistance, no appearance defects such as bubbles and warping, good batch stability and is suitable for mass production of medium and high-end sealing and damping rubber-plastic products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a plastic rubber and its vulcanization molding process. Background Technology

[0002] Rubber-plastic blended vulcanized materials, leveraging the high elasticity of rubber and the rigidity and dimensional stability of plastics, are widely used in industrial applications such as sealing, shock absorption, wear resistance, and general-purpose rubber and plastic products. They represent a crucial material system for replacing traditional single-material rubber or single-material plastics. However, with increasing demands for dimensional stability, oil resistance, compression set resistance, and batch consistency in the automotive, equipment manufacturing, oil seal, and shock absorption components industries, traditional processes—primarily involving direct blending of unmodified natural rubber with plastics, single-sulfur vulcanization systems, one-time mixing, and isothermal vulcanization—while meeting the production needs of some conventional low-end products, are increasingly revealing problems when upgrading to mid-to-high-end products. These problems include insufficient interfacial compatibility, unstable filler dispersion, difficulty in precisely controlling crosslinking reactions, and numerous molding defects, making it difficult to consistently meet the mass production standards for mid-to-high-end rubber and plastic products.

[0003] Specifically, in the vulcanization process of rubber-plastic blends for mid-to-high-end products, the polarity difference between ordinary natural rubber and plastic components such as high-density polyethylene is significant. Furthermore, the high surface activity and tendency of inorganic fillers to agglomerate easily lead to weak interphase bonding between the rubber and plastic phases, uneven filler dispersion, and localized stress concentration. This results in large fluctuations in the tensile strength, tear strength, impact toughness, and oil resistance of the finished product, and insufficient batch-to-batch consistency. Simultaneously, a single vulcanization system cannot simultaneously achieve both rubber bulk crosslinking and rubber-plastic interphase reinforcement. During production, early scorching, localized under-vulcanization, or over-vulcanization can easily occur, leading to uneven crosslinking network density. This results in insufficient aging resistance and compression set resistance in the products, making them prone to deformation, cracking, or sealing failure during long-term service.

[0004] From the perspective of industrial mass production, if existing processes still adopt a single temperature and pressure vulcanization and setting mode, the internal gas of the rubber compound is not fully discharged, and the internal stress generated during mixing and molding is difficult to release. This leads to appearance defects such as bubbles, pits, and material shortages on the surface of the finished product, and warping and unstable dimensional accuracy after demolding. Existing improvement methods mostly focus on simply adjusting the raw material ratio or a single process parameter, lacking a systematic and coordinated design between rubber modification, filler surface treatment, graded mixing, vulcanizing agent addition methods, degassing vulcanization, and curing molding. It is difficult to simultaneously take into account material mechanical stability, appearance yield, batch consistency, and long-term service performance. Summary of the Invention

[0005] In view of this, the purpose of the present invention is to provide a plastic rubber and its vulcanization molding process.

[0006] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a vulcanization molding process for plastic rubber, comprising the following preparation steps: S1: Natural raw rubber is put into a two-roll mill for thin-pass pre-activation, then dicumyl peroxide, glycidyl methacrylate, polyetheramine and anhydrous ethanol are added, and the reaction is carried out in stages under a closed nitrogen atmosphere. After the reaction is completed, it is dried to obtain modified natural rubber. S2: Fumed silica and attapulgite clay are mixed and sieved to obtain pretreated filler; the pretreated filler, fatty alcohol polyoxyethylene ether AEO-9, and n-dodecylphosphonic acid are dispersed in deionized water to complete chelation coating to obtain chelated coating dispersion; maleic anhydride-grafted EPDM rubber is added to cyclohexane for pre-swelling to obtain maleic anhydride-grafted EPDM rubber dispersion; the maleic anhydride-grafted EPDM rubber dispersion is added to the chelated coating dispersion for heat setting coating, and then subjected to desolventizing under reduced pressure, vacuum drying and sieving to obtain composite functional filler; S3: Modified natural rubber and high-density polyethylene are mixed and then subjected to a first-stage high-temperature internal mixing process to melt the high-density polyethylene and blend it with the modified natural rubber. Subsequently, composite functional fillers and naphthenic oil are added and subjected to a second-stage internal mixing process to obtain masterbatch. After cooling the masterbatch, it is transferred to a two-roll mill and the main vulcanization group, interface vulcanization group, zinc oxide, stearic acid, and antioxidant are added and subjected to low-temperature two-roll mixing to obtain compound. S4: Spread the mixed rubber compound flat and let it stand, then perform constant temperature and sealed curing to obtain the cured rubber compound; place the cured rubber compound in a mold, first pre-press to degas, then perform constant pressure gradient vulcanization, and after cooling, demold to obtain plastic rubber.

[0007] Further, the raw materials used in S1, by weight, are: 95-105 parts of natural raw rubber, 1.0-1.4 parts of dicumyl peroxide, 4.2-4.8 parts of glycidyl methacrylate, 3.5-4.1 parts of polyetheramine, and 18-22 parts of anhydrous ethanol.

[0008] Further, the raw materials used in S2, by weight, are as follows: 13-15 parts fumed silica, 6-8 parts attapulgite clay, 2.2-2.6 parts n-dodecylphosphonic acid, 2.4-2.8 parts maleic anhydride-grafted EPDM rubber, 0.7-0.9 parts fatty alcohol polyoxyethylene ether AEO-9, 220-280 parts deionized water, and 18-22 parts cyclohexane.

[0009] Further, the raw materials used in S3, by weight, are as follows: 54-58 parts of grafted modified natural rubber, 22-24 parts of high-density polyethylene, 22-24 parts of composite functional filler, 3.6-4.0 parts of naphthenic oil, 2.6-3.2 parts of main vulcanization group, 1.4-1.8 parts of interface vulcanization group, 3.4-3.8 parts of zinc oxide, 1.0-1.2 parts of stearic acid, and 0.6-0.8 parts of antioxidant.

[0010] Furthermore, the antioxidant is antioxidant 1076.

[0011] Furthermore, the main vulcanization group is composed of sulfur and accelerator CBS in a weight ratio of 1.7-2.1:1; the interface vulcanization group is composed of accelerator TMTM, dicumyl peroxide, and trimethylolpropane triacrylate in a weight ratio of 1.25-2.8:0.6-0.8:1.

[0012] Further, the process parameters for step S1 are as follows: open mill roll temperature 40-44℃, roll gap 0.32-0.38mm, number of thin passes 10-14 times, each thin pass lasting 25-35s, rubber material residence time 8-12s between two adjacent thin passes, and rubber material residence time 8-12min after thin passes; the segmented heating reaction is carried out in a closed nitrogen atmosphere, with the first stage reaction temperature at 126-134℃ and reaction time at 1.8-2.2h, and the second stage reaction temperature at 92-98℃ and reaction time at 1.3-1.7h.

[0013] In step S2, the chelation coating temperature is 53-57℃ and the chelation coating time is 1.3-1.7h; the heat setting coating temperature is 53℃-74℃ and the heat setting coating time is 2.8-3.2h.

[0014] Furthermore, in step S2, the fumed silica and attapulgite clay are mixed and then sieved using a 300-mesh sieve.

[0015] Further, in step S2, maleic anhydride-grafted EPDM rubber is added to cyclohexane and pre-dissolved at 55-60°C to obtain a maleic anhydride-grafted EPDM rubber dispersion. Under high-speed shearing conditions, the maleic anhydride-grafted EPDM rubber dispersion is added to the chelation-coated dispersion at a speed of 1200-1400 r / min.

[0016] Further, the descaling conditions in step S2 are: temperature 45-55℃, vacuum degree -0.06 to -0.085MPa, and descaling time 35-60min; Furthermore, the vacuum drying conditions in step S2 are: temperature 50-60℃, vacuum degree -0.085 to -0.095MPa, and drying to constant weight.

[0017] Further, the two-stage internal mixing and low-temperature open mill mixing process in step S3 is as follows: the first stage internal mixing temperature is 138-145℃, the stirring speed is 220-260r / min, and the mixing time is 6-8min; the second stage internal mixing temperature is 126-134℃, the stirring speed is 200-240r / min, and the mixing time is 8-10min; during the low-temperature open mill mixing, the open mill roll temperature is 48-56℃, the roll gap is 0.6-0.8mm, the main vulcanizing group is added first and mixed for 1.8-2.2min, and then the interface vulcanizing group, zinc oxide, stearic acid, and antioxidant are added and mixed for 2.3-2.7min. The sheet temperature of the mixed rubber is controlled at 65℃ or below.

[0018] Furthermore, in step S4, the rubber compound is laid out and allowed to stand: the mixed rubber is spread out evenly and left to stand at room temperature for 20-24 minutes.

[0019] Furthermore, in step S4, constant temperature and sealed curing is performed: the rubber compound that has been left to stand is transferred to a sealed environment, the curing temperature is 45-49℃, and the constant temperature holding time is 30-34 minutes.

[0020] Furthermore, in step S4, the gradient vulcanization process is as follows: after the cured rubber compound is loaded into the mold, it is first pre-pressed at 5.1-5.5 MPa for 1-2 minutes, and then depressurized and vented 3-4 times, each time for 8-12 seconds; after venting, the constant pressure of 5.1-5.5 MPa is maintained for gradient vulcanization. The first stage vulcanization temperature is 129-133℃ and the holding temperature is 5-7 minutes; the second stage vulcanization temperature is 142-146℃ and the holding temperature is 4-5 minutes; and the third stage vulcanization temperature is 151-155℃ and the holding temperature is 2-4 minutes.

[0021] Secondly, the present invention provides a plastic rubber prepared by the above-mentioned vulcanization molding process.

[0022] The beneficial effects of this invention are: This invention first modifies natural rubber by combining glycidyl methacrylate with polyetheramine, introducing polar active groups into the rubber molecular chain and significantly improving the interfacial affinity between natural rubber and high-density polyethylene. Simultaneously, it synergistically chelates and coats fumed silica and attapulgite fillers using dodecylphosphonic acid and fatty alcohol polyoxyethylene ether AEO-9, and then heat-sets and coats the fillers using maleic anhydride-grafted EPDM pre-melted rubber solution, completing the organic modification of the inorganic filler surface, reducing the filler surface activation energy, and preventing filler agglomeration in the rubber-plastic matrix. The dual synergistic effect of modified rubber and modified fillers eliminates phase separation and delamination defects in the rubber-plastic blend system, resulting in a uniform and stable internal structure in the finished product. This fundamentally solves the industry pain points of large fluctuations in mechanical properties and low yield rates in traditional processes.

[0023] This invention employs a two-component vulcanization system consisting of a main vulcanization group and an interface vulcanization group. Combined with a staged mixing method involving high-temperature intensive mixing and cooling open mill vulcanization, this ensures sufficient melting and dispersion of high-density polyethylene while preventing premature decomposition or scorching of the vulcanizing agent during the high-temperature intensive mixing stage. The main vulcanization component is responsible for cross-linking and molding within the matrix, while the interface vulcanization component directionally strengthens the cross-linking and bonding between the rubber and plastic phases, forming a uniform, continuous, and complete three-dimensional cross-linked network. This effectively reduces the tendency of products to compress, improves the material's resistance to aging and cracking, extends the service life of rubber and plastic sealing and shock-absorbing products, and addresses the shortcomings of traditional products that are prone to deformation and failure.

[0024] This invention employs a segmented differentiated mixing and open mill feeding method. First, the rubber-plastic matrix is ​​blended at high temperature to fully melt the high-density polyethylene. Then, reinforcing fillers are added for secondary dispersion. Finally, vulcanization aids are introduced during the low-temperature open milling stage to reduce premature vulcanization caused by processing temperature increases. After mixing, a room-temperature settling and closed-loop constant-temperature curing process is added to fully release the internal mixing stress of the rubber compound. In the molding stage, pre-pressure venting, three-stage stepped temperature vulcanization, and constant pressure holding after venting ensure that the internal gas of the rubber compound is fully discharged and the material flows uniformly within the mold. Compared to traditional one-time mixing and constant-temperature vulcanization processes, this method reduces appearance defects such as bubbles, pitting, material shortages, and demolding warping in the finished product, stabilizes the dimensional accuracy of the molded product, and ensures both appearance quality and dimensional consistency for mass industrial production. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in this invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.

[0026] Figure 1 The image shows a scanning electron microscope (SEM) image of the low-temperature brittle fracture of the plastic rubber prepared in Example 1 of this invention, with a scale bar of 20 μm.

[0027] Figure 2 This is a magnified view of the surface of the plastic rubber prepared in Example 1 of the present invention. Detailed Implementation

[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0029] The natural raw rubber used in this invention is of the STRXL type and was purchased from Jinan Yuanbaolai Chemical Technology Co., Ltd.

[0030] The glycidyl methacrylate used in this invention was purchased from Shandong Xinshunli Chemical Technology Co., Ltd.

[0031] The polyetheramine used in this invention has an amine value of 1000 and was purchased from Wuhan Jiyesheng Chemical Co., Ltd.

[0032] The fumed silica used in this invention is named CAB-O-SILMS60, model MS60, and was purchased from Shanghai Zhenlishi Network Technology Co., Ltd.

[0033] The attapulgite clay used in this invention has a particle size of 1250-1800 mesh and was purchased from Lingshou County Baibo Mineral Products Processing Plant.

[0034] The fatty alcohol polyoxyethylene ether used in this invention is AEO-9, which was purchased from Wuhan Jiyesheng Chemical Co., Ltd.

[0035] The dodecylphosphonic acid used in this invention was purchased from Hubei Jusheng Technology Co., Ltd.

[0036] The maleic anhydride-grafted EPDM rubber used in this invention is grade TF-EP23 and was purchased from Kaiming Plastics (Dongguan) Co., Ltd.

[0037] The high-density polyethylene used in this invention is grade M80064S, purchased from Shanghai Hongchao Plastic Raw Materials Co., Ltd.

[0038] The naphthenic oil used in this invention is model N4010, purchased from Shandong Zhuyou Lubrication Technology Co., Ltd.

[0039] The accelerator CBS used in this invention was purchased from Hubei Qiansheng Biotechnology Co., Ltd.

[0040] The rubber accelerator TMTM used in this invention was purchased from Ba Shifu (Shanghai) Biomedical Technology Co., Ltd.

[0041] The trimethylolpropane triacrylate used in this invention was purchased from Greenlink (Jining) Chemical Technology Co., Ltd.

[0042] The zinc oxide used in this invention was purchased from Jinan Haicheng Chemical Co., Ltd.

[0043] The antioxidant used in this invention is Irganox1076, which was purchased from Dongguan Hongli Chemical Technology Co., Ltd.

[0044] Example 1 A vulcanization molding process for plastic rubber includes the following preparation steps: S1: 95 parts by weight of natural raw rubber, 1.0 part by weight of dicumyl peroxide, 4.2 parts by weight of glycidyl methacrylate, 3.5 parts by weight of polyetheramine, and 18 parts by weight of anhydrous ethanol; the natural raw rubber is fed into a two-roll mill at a roller temperature of 40℃ and a roller gap of 0.32mm, and pre-activated by passing it through a thin mill 10 times, each pass lasting 25s, with an 8s interval between passes. After passing through the mill, the rubber compound is left to stand under nitrogen protection for 8 minutes; dicumyl peroxide, glycidyl methacrylate, polyetheramine, and anhydrous ethanol are added, and the mixture is placed in a sealed reactor. Under nitrogen protection, the first stage reaction is carried out at 126℃ for 1.8h, and the second stage reaction is carried out at 92℃ for 1.3h; after the reaction is completed, the mixture is vacuum dried at 58℃ to obtain modified natural rubber; S2: Take 13 parts by weight of fumed silica, 6 parts by weight of 1250-mesh attapulgite clay, 2.2 parts by weight of n-dodecylphosphonic acid, 2.4 parts by weight of maleic anhydride-grafted EPDM rubber, 0.7 parts by weight of fatty alcohol polyoxyethylene ether AEO-9, 220 parts by weight of deionized water, and 18 parts by weight of cyclohexane; mix the fumed silica and 1250-mesh attapulgite clay, and sieve through a 300-mesh sieve to obtain the pretreated filler; add the pretreated filler, fatty alcohol polyoxyethylene ether AEO-9, and n-dodecylphosphonic acid to deionized water, and chelate and coat at 53℃ for 1.3 hours; add the maleic anhydride-grafted EPDM rubber... Ethylene propylene rubber was added to cyclohexane and pre-dissolved at 55°C to obtain a maleic anhydride-grafted EPDM rubber dispersion. This dispersion was then added to a chelating and coating dispersion under high-speed shear at 1200 r / min, and heat-set and coated at 53°C for 2.8 h. After heat-setting and coating, the mixture was desolvated under reduced pressure at 45°C and a vacuum of -0.06 MPa for 35 min, and then vacuum-dried to constant weight at 50-60°C and a vacuum of -0.085 MPa. The dried product was sieved through a 300-mesh sieve to obtain the composite functional filler. S3: 54 parts by weight of modified natural rubber, 22 parts by weight of high-density polyethylene, 22 parts by weight of composite functional filler, 3.6 parts by weight of naphthenic oil, 2.6 parts by weight of main vulcanizing group, 1.4 parts by weight of interface vulcanizing group, 3.4 parts by weight of zinc oxide, 1.0 part by weight of stearic acid, and 0.6 parts by weight of antioxidant; wherein the main vulcanizing group is composed of sulfur and accelerator CBS in a weight ratio of 1.7:1; the interface vulcanizing group is composed of accelerator TMTM, dicumyl peroxide, and trimethylolpropane triacrylate in a weight ratio of 1.25:0.6:1; the modified natural rubber and high-density polyethylene are fed into a mixing mill. The high-density polyethylene was melted and blended with modified natural rubber at 220 r / min for 6 minutes at 138℃. Then, composite functional fillers and naphthenic oil were added, and the mixture was stirred at 200 r / min for 8 minutes at 126℃ to obtain the masterbatch. The masterbatch was cooled to 50℃ and then transferred to a two-roll mill with a roll temperature of 48℃ and a roll gap of 0.6 mm. The main vulcanizing group was added and mixed for 1.8 minutes. Then, the interface vulcanizing group, zinc oxide, stearic acid, and antioxidant 1076 were added and mixed for 2.3 minutes. After passing through a thin sheet 3 times, the sheeting temperature of the compound was controlled to be ≤65℃ to obtain the compound. S4: The compound rubber is laid flat and allowed to stand at room temperature for 20 minutes, then transferred to a sealed environment and cured at 45℃ for 30 minutes. After the cured rubber is loaded into the mold, it is first pre-pressed at 5.1MPa for 1 minute, and then depressurized and vented 3 times, each time for 8 seconds. After venting, the rubber is vulcanized at a gradient of 5.1MPa throughout the process: 129℃ for 5 minutes, 142℃ for 4 minutes, and 151℃ for 2 minutes. After vulcanization, it is cooled and demolded to obtain plastic rubber.

[0045] Example 2 A vulcanization molding process for plastic rubber includes the following preparation steps: S1: Take 100 parts by weight of natural raw rubber, 1.2 parts by weight of dicumyl peroxide, 4.5 parts by weight of glycidyl methacrylate, 3.8 parts by weight of polyetheramine, and 20 parts by weight of anhydrous ethanol. Put the natural raw rubber into a two-roll mill with a roller temperature of 42℃ and a roller gap of 0.35mm. Perform 12 thin passes to complete the pre-activation, each pass lasting 30s, with a 10s interval between two passes. After passing through the mill, let the rubber compound stand under nitrogen protection for 10 minutes. Add dicumyl peroxide, glycidyl methacrylate, polyetheramine, and anhydrous ethanol. Place the mixture in a sealed reactor and react at 130℃ for 2.0h in the first stage and at 95℃ for 1.5h in the second stage under nitrogen protection. After the reaction is completed, vacuum dry at 60℃ to obtain modified natural rubber. S2: 14 parts by weight of fumed silica, 7 parts by weight of 1500-mesh attapulgite clay, 2.4 parts by weight of n-dodecylphosphonic acid, 2.6 parts by weight of maleic anhydride-grafted EPDM rubber, 0.8 parts by weight of fatty alcohol polyoxyethylene ether AEO-9, 250 parts by weight of deionized water, and 20 parts by weight of cyclohexane; Fumed silica and 1500-mesh attapulgite clay are mixed and sieved through a 300-mesh sieve to obtain pretreated filler; the pretreated filler, fatty alcohol polyoxyethylene ether AEO-9, and n-dodecylphosphonic acid are added to deionized water and chelated at 55°C for 1.5 hours; the maleic anhydride-grafted EPDM rubber is then... Ethylene propylene rubber was added to cyclohexane and pre-dissolved at 57°C to obtain a maleic anhydride-grafted EPDM dispersion. This dispersion was then added to a chelating and coating dispersion under high-speed shear at 1300 r / min, and heat-set at 63°C for 3.0 h. After heat-setting and coating, the mixture was desolvated under reduced pressure at 50°C and a vacuum of -0.075 MPa for 48 min, and then vacuum-dried at 55°C and a vacuum of -0.090 MPa to constant weight. The dried product was sieved through a 300-mesh sieve to obtain the composite functional filler. S3: 56 parts by weight of modified natural rubber, 23 parts by weight of high-density polyethylene, 23 parts by weight of composite functional filler, 3.8 parts by weight of naphthenic oil, 2.9 parts by weight of main vulcanizing group, 1.6 parts by weight of interface vulcanizing group, 3.6 parts by weight of zinc oxide, 1.1 parts by weight of stearic acid, and 0.7 parts by weight of antioxidant; wherein the main vulcanizing group is composed of sulfur and accelerator CBS in a weight ratio of 1.9:1; the interface vulcanizing group is composed of accelerator TMTM, dicumyl peroxide, and trimethylolpropane triacrylate in a weight ratio of 2.1:0.7:1; the modified natural rubber and high-density polyethylene are fed into a mixing mill. The high-density polyethylene was melted and blended with modified natural rubber at 142℃ and 240r / min for 7 minutes in the first stage. Then, composite functional fillers and naphthenic oil were added, and the mixture was stirred at 130℃ and 220r / min for 9 minutes in the second stage to obtain the masterbatch. The masterbatch was cooled to 55℃ and then transferred to a two-roll mill with a roll temperature of 52℃ and a roll gap of 0.7mm. The main vulcanizing group was added and mixed for 2.0 minutes. Then, the interface vulcanizing group, zinc oxide, stearic acid, and antioxidant 1076 were added and mixed for 2.5 minutes. After passing through the thin sheet three times, the sheet was extruded and the sheet temperature of the compound was controlled to be ≤65℃ to obtain the compound. S4: The compound rubber is laid flat and allowed to stand at room temperature for 22 minutes, then transferred to a sealed environment and cured at 47℃ for 32 minutes. After the cured rubber is loaded into the mold, it is first pre-pressed at 5.3MPa for 1.5 minutes, and then depressurized and vented 3 times, each time for 10 seconds. After venting, the rubber is vulcanized at a gradient of 5.3MPa throughout the process: 131℃ for 6 minutes, 144℃ for 4.5 minutes, and 153℃ for 3 minutes. After vulcanization, it is cooled and demolded to obtain plastic rubber.

[0046] Example 3 A vulcanization molding process for plastic rubber includes the following preparation steps: S1: 105 parts by weight of natural raw rubber, 1.4 parts by weight of dicumyl peroxide, 4.8 parts by weight of glycidyl methacrylate, 4.1 parts by weight of polyetheramine, and 22 parts by weight of anhydrous ethanol were prepared. The natural raw rubber was fed into a two-roll mill at a roller temperature of 44℃ and a roller gap of 0.38 mm. The rubber was pre-activated by passing it through a thin mill 14 times, with each pass lasting 35 seconds and a 12-second interval between passes. After passing through the mill, the rubber was allowed to stand under nitrogen protection for 12 minutes. Dicumyl peroxide, glycidyl methacrylate, polyetheramine, and anhydrous ethanol were added and placed in a sealed reactor. The reaction was carried out under nitrogen protection for 2.2 hours at 134℃ in the first stage and 1.7 hours at 98℃ in the second stage. After the reaction was completed, the rubber was dried under vacuum at 62℃ to obtain modified natural rubber. S2: 15 parts by weight of fumed silica, 8 parts by weight of 1800-mesh attapulgite clay, 2.6 parts by weight of n-dodecylphosphonic acid, 2.8 parts by weight of maleic anhydride-grafted EPDM rubber, 0.9 parts by weight of fatty alcohol polyoxyethylene ether AEO-9, 280 parts by weight of deionized water, and 22 parts by weight of cyclohexane; Fumed silica and 1800-mesh attapulgite clay are mixed and sieved through a 300-mesh sieve to obtain pretreated filler; the pretreated filler, fatty alcohol polyoxyethylene ether AEO-9, and n-dodecylphosphonic acid are added to deionized water and chelated at 57°C for 1.7 hours; the maleic anhydride-grafted EPDM rubber is then... Ethylene propylene rubber was added to cyclohexane and pre-dissolved at 60°C to obtain a maleic anhydride-grafted EPDM dispersion. This dispersion was then added to a chelating and coating dispersion under high-speed shear at 1400 r / min, and heat-set at 74°C for 3.2 h. After heat-setting and coating, the mixture was desolvated under reduced pressure at 55°C and a vacuum of -0.085 MPa for 60 min, and then vacuum-dried at 60°C and a vacuum of -0.095 MPa to constant weight. The dried product was sieved through a 300-mesh sieve to obtain the composite functional filler. S3: 58 parts by weight of modified natural rubber, 24 parts by weight of high-density polyethylene, 24 parts by weight of composite functional filler, 4.0 parts by weight of naphthenic oil, 3.2 parts by weight of main vulcanizing group, 1.8 parts by weight of interface vulcanizing group, 3.8 parts by weight of zinc oxide, 1.2 parts by weight of stearic acid, and 0.8 parts by weight of antioxidant; wherein the main vulcanizing group is composed of sulfur and accelerator CBS in a weight ratio of 2.1:1; the interface vulcanizing group is composed of accelerator TMTM, dicumyl peroxide, and trimethylolpropane triacrylate in a weight ratio of 2.8:0.8:1; the modified natural rubber and high-density polyethylene are fed into a mixing mill, 1 The high-density polyethylene was melted and blended with modified natural rubber at 260 r / min for 8 minutes at 45℃. Then, composite functional fillers and naphthenic oil were added, and the mixture was stirred at 240 r / min for 10 minutes at 134℃ to obtain the masterbatch. The masterbatch was cooled to 60℃ and then transferred to a two-roll mill with a roll temperature of 56℃ and a roll gap of 0.8 mm. The main vulcanizing group was added and mixed for 2.2 minutes. Then, the interface vulcanizing group, zinc oxide, stearic acid, and antioxidant 1076 were added and mixed for 2.7 minutes. After passing through a thin sheet 3 times, the sheeting temperature of the compound was controlled to be ≤65℃ to obtain the compound. S4: The compound rubber is laid flat and allowed to stand at room temperature for 24 minutes, then transferred to a sealed environment and cured at a constant temperature of 49℃ for 34 minutes; after the cured rubber is loaded into the mold, it is first pre-pressed at 5.5MPa for 2 minutes, and then depressurized and vented 4 times, each time for 12 seconds; after venting, the entire process is maintained at a gradient of 5.5MPa for vulcanization: 133℃ for 5 minutes, 146℃ for 5 minutes, and 155℃ for 4 minutes; after vulcanization, it is cooled and demolded to obtain plastic rubber.

[0047] Comparative Example 1 Compared with Example 1, this comparative example replaces "glycidyl methacrylate" with an equal mass of "polyetheramine"; all other steps and parameters are the same, and will not be repeated in this comparative example. Finally, a plastic rubber is obtained.

[0048] Comparative Example 2 Compared with Example 1, this comparative example replaces "polyetheramine" with an equal mass of "glycidyl methacrylate"; all other steps and parameters are the same, and will not be repeated in this comparative example. Finally, a plastic rubber is obtained.

[0049] Comparative Example 3 Compared with Example 1, this comparative example replaces "dodecylphosphonic acid" with an equal mass of "fatty alcohol polyoxyethylene ether AEO-9"; the remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, a plastic rubber is obtained.

[0050] Comparative Example 4 Compared with Example 1, this comparative example replaces "fatty alcohol polyoxyethylene ether AEO-9" with an equal mass of "dodecylphosphonic acid"; the remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, a plastic rubber is obtained.

[0051] Comparative Example 5 Compared with Example 1, this comparative example replaces "attapulgite clay" with an equal mass of "fumed silica"; the remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, a plastic rubber is obtained.

[0052] Comparative Example 6 Compared with Example 1, this comparative example replaces "fumed silica" with an equal mass of "attapulgite clay"; all other steps and parameters are the same, and will not be repeated in this comparative example. Finally, a plastic rubber is obtained.

[0053] Comparative Example 7 Compared with Example 1, this comparative example replaces the "interface vulcanization group" with an equal mass of "main vulcanization group"; the remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, plastic rubber is obtained.

[0054] Comparative Example 8 Compared with Example 1, this comparative example replaces "trimethylolpropane triacrylate" with an equal mass of "accelerator TMTM"; all other steps and parameters are the same, and will not be repeated in this comparative example. Finally, a plastic rubber is obtained.

[0055] Comparative Example 9 Compared with Example 1, this comparative example replaces "accelerator CBS" with an equal mass of "sulfur"; all other steps and parameters are the same, and will not be repeated in this comparative example. Finally, plastic rubber is obtained.

[0056] The plastic rubbers prepared in Examples 1-3 and Comparative Examples 1-9 were tested, and the results are recorded in Table 1.

[0057] Tensile strength and elongation at break: In accordance with GB / T528-2009, a universal tensile testing machine was used with type 1 dumbbell specimens at a tensile rate of 500 mm / min. The breaking load and elongation data were recorded to evaluate the tensile toughness and interfacial bonding effect of the material.

[0058] Right-angle tear strength: According to GB / T529-2008, the tear test was carried out using the Type A right-angle standard specimen, and the tear strength was calculated by reading the peak load to compare the quality of filler dispersion.

[0059] Shore D hardness: According to GB / T531.1-2018 Shore hardness test specification, a flat sample with a thickness of 6.0±0.2mm is used, and the hardness is tested at multiple points on the sample. The average value is taken to characterize the rigidity of the material.

[0060] Compression permanent deformation: According to GB / T7759.1-2015, type A specimens were used, and the specimens were placed at a constant temperature of 70℃ for 22 hours with a 25% compression ratio. The thickness was measured after cooling, and the deformation rate was calculated.

[0061] Impact strength of simply supported beam at room temperature: According to GB / T1043.1-2008, the impact test was carried out using a 1eA type standard specimen with a specimen size of 80mm×10mm×4mm and a notch bottom radius of 0.25±0.05mm to characterize the impact toughness of the material.

[0062] Oil swelling resistance: According to GB / T1690-2010, the mass change was calculated by immersing in standard oil #1 at room temperature for 72 hours and weighing.

[0063] Table 1: Test data for plastics and rubber

[0064] According to the test results in Table 1, the plastic rubber prepared in Examples 1-3 of this invention exhibits excellent comprehensive performance in terms of tensile strength, elongation at break, right-angle tear strength, resistance to compression set, impact toughness, and oil resistance. All performance indicators are balanced and outstanding, and the overall level is significantly better than that of the comparative examples. It can fully meet the stringent application requirements of mechanical reliability and long-term service stability for mid-to-high-end rubber and plastic sealing, shock absorption, and wear-resistant products.

[0065] Figure 1 The image shows a scanning electron microscope (SEM) image of the low-temperature brittle fracture of the plastic rubber prepared in Example 1. The image reveals that the brittle fracture surface of the material has a rough morphology, exhibiting typical ductile fracture characteristics, with numerous tear ridges and traces of plastic deformation throughout the fracture surface. The rubber-plastic two-phase interface is tightly bonded, with no obvious phase separation or interface peeling. The inorganic filler is uniformly dispersed in the matrix, without large-scale agglomerates.

[0066] As can be seen from the comparison between Example 1 and Comparative Examples 1 and 2, when natural rubber is modified by using polyetheramine or glycidyl methacrylate alone, the mechanical strength, fracture toughness, and deformation resistance of the material all deteriorate significantly. This is because the synergistic grafting modification of glycidyl methacrylate and polyetheramine can introduce polar reactive functional groups and flexible segments into the natural rubber molecular chain, effectively improving the interfacial compatibility between the rubber phase and the high-density polyethylene phase, and constructing a stable two-phase transition bonding layer; the absence of either component will prevent the formation of a perfect interfacial compatibility effect, easily causing defects in the rubber-plastic two-phase interface separation, resulting in a significant decrease in the overall performance of the material.

[0067] A comparison of Example 1 with Comparative Examples 3 and 4 shows that replacing dodecylphosphonic acid with fatty alcohol polyoxyethylene ether AEO-9 with each other reduces both the reinforcing effect of the filler and the oil penetration resistance of the material. The chelate coating system synergistically constructed by these two components can uniformly organically modify the surface of the inorganic filler, reducing its surface energy and significantly improving its dispersion uniformity in the rubber-plastic matrix, thus avoiding stress concentration defects caused by filler agglomeration. Simultaneously, it can enhance the interfacial bonding force between the filler particles and the organic matrix, fully utilizing the reinforcing effect of the filler and simultaneously improving the material's mechanical strength and media resistance.

[0068] A comparison of Example 1 with Comparative Examples 5 and 6 shows that when fumed silica or attapulgite clay is used alone as a reinforcing filler, the overall mechanical properties and deformation resistance of the material are inferior to those of the combination of the two. This is because fumed silica has a high specific surface area and excellent nano-reinforcing activity, which can significantly improve the matrix modulus; however, its particles have extremely high surface energy, making them prone to secondary agglomeration and forming localized stress concentration points in the absence of synergistic components. Attapulgite clay, on the other hand, has a fibrous morphology and possesses the potential for stress transfer and microcrack deflection, but its reinforcing activity is insufficient when used alone, making it difficult to construct a complete filler network. When the two are combined, the spherical fumed silica and the fibrous attapulgite clay form a spatially complementary "sphere-fiber" synergistic filling structure, ensuring high reinforcing activity while improving the material's resistance to crack propagation through the bridging and crack-inhibiting effects of the fibrous particles. When this compound system works synergistically with the organic coating of phosphonic acid and surfactants, the surface energy of the filler is further reduced and the dispersion uniformity is significantly improved, thereby achieving a better balance between strength, toughness and resistance to compression deformation.

[0069] As can be seen from the comparison between Example 1 and Comparative Examples 7-9, disrupting the compositional balance of the two-component vulcanization system—whether by completely replacing the interfacial vulcanization group with the main vulcanization group, removing the acrylate crosslinking active component from the interfacial vulcanization group, or breaking the compound ratio of sulfur and accelerator in the main vulcanization group—will lead to a significant deterioration in the material's compression set resistance and a decrease in long-term service stability. The underlying mechanism is that the hierarchical vulcanization system of "main vulcanization group + interfacial vulcanization group" constructed in this invention has a clear division of labor and synergistic effect. The main vulcanization group (sulfur + CBS) is responsible for constructing a uniform sulfur crosslinking network within the rubber bulk phase, providing the material's basic elasticity and resilience. In the interfacial vulcanization group, dicumyl peroxide homolytically cleaves at the vulcanization temperature to generate free radicals, in situ initiating the polymerization of multifunctional double bonds of trimethylolpropane triacrylate, forming a highly reactive "bridging branch layer" at the rubber-plastic interface. The accelerator TMTM, by adjusting the vulcanization rate, ensures that the interfacial crosslinking and bulk crosslinking are matched on a time scale. When the interfacial vulcanization group is completely replaced by the main vulcanization group, the rubber-plastic interface lacks chemical bonding, and the two phases are easily separated under stress. When the acrylate component is removed, sufficient crosslinking density cannot be formed at the interface, resulting in insufficient interfacial bonding strength. When the proportion within the main vulcanization group is unbalanced, the vulcanization rate mismatch leads to uneven crosslinking network density and an increase in internal stress concentration points. All three factors fundamentally destroy the hierarchical network structure of "bulk crosslinking-interfacial reinforcement" in this invention. Under long-term compression service conditions, the crosslinking network cannot effectively constrain the slippage and rearrangement of molecular chains, resulting in a significant increase in the compression set rate, making it difficult to meet the stringent requirements for long-term dimensional stability in sealing and shock-absorbing products.

[0070] The above description is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.

Claims

1. A vulcanization molding process for plastic rubber, characterized in that, The preparation steps include the following: S1: Natural raw rubber is put into a two-roll mill for thin-pass pre-activation, then dicumyl peroxide, glycidyl methacrylate, polyetheramine and anhydrous ethanol are added, and the reaction is carried out in stages under a closed nitrogen atmosphere. After the reaction is completed, it is dried to obtain modified natural rubber. S2: Fumed silica and attapulgite clay are mixed and sieved to obtain pretreated filler; the pretreated filler, fatty alcohol polyoxyethylene ether AEO-9, and n-dodecylphosphonic acid are dispersed in deionized water to complete chelation coating to obtain chelated coating dispersion; maleic anhydride-grafted EPDM rubber is added to cyclohexane for pre-swelling to obtain maleic anhydride-grafted EPDM rubber dispersion; the maleic anhydride-grafted EPDM rubber dispersion is added to the chelated coating dispersion for heat setting coating, and then subjected to desolventizing under reduced pressure, vacuum drying and sieving to obtain composite functional filler; S3: Modified natural rubber and high-density polyethylene are mixed and then subjected to a first-stage high-temperature internal mixing process to melt the high-density polyethylene and blend it with the modified natural rubber. Subsequently, composite functional fillers and naphthenic oil are added and subjected to a second-stage internal mixing process to obtain masterbatch. After cooling the masterbatch, it is transferred to a two-roll mill and the main vulcanization group, interface vulcanization group, zinc oxide, stearic acid, and antioxidant are added and subjected to low-temperature two-roll mixing to obtain compound. S4: Spread the mixed rubber compound flat and let it stand, then perform constant temperature and sealed curing to obtain the cured rubber compound; place the cured rubber compound in a mold, first pre-press to degas, then perform constant pressure gradient vulcanization, and after cooling, demold to obtain plastic rubber.

2. The vulcanization molding process for plastic rubber according to claim 1, characterized in that, The raw materials used in S1, by weight, are as follows: 95-105 parts of natural raw rubber, 1.0-1.4 parts of dicumyl peroxide, 4.2-4.8 parts of glycidyl methacrylate, 3.5-4.1 parts of polyetheramine, and 18-22 parts of anhydrous ethanol.

3. The vulcanization molding process for plastic rubber according to claim 1, characterized in that, The raw materials used in S2, by weight, are as follows: 13-15 parts fumed silica, 6-8 parts attapulgite clay, 2.2-2.6 parts n-dodecylphosphonic acid, 2.4-2.8 parts maleic anhydride-grafted EPDM rubber, 0.7-0.9 parts fatty alcohol polyoxyethylene ether AEO-9, 220-280 parts deionized water, and 18-22 parts cyclohexane.

4. The vulcanization molding process for plastic rubber according to claim 1, characterized in that, The raw materials used in S3, by weight, are as follows: 54-58 parts grafted modified natural rubber, 22-24 parts high-density polyethylene, 22-24 parts composite functional filler, 3.6-4.0 parts naphthenic oil, 2.6-3.2 parts main vulcanization group, 1.4-1.8 parts interface vulcanization group, 3.4-3.8 parts zinc oxide, 1.0-1.2 parts stearic acid, and 0.6-0.8 parts antioxidant.

5. The vulcanization molding process for plastic rubber according to claim 4, characterized in that, The main vulcanization group is composed of sulfur and accelerator CBS in a weight ratio of 1.7-2.1:1; the interface vulcanization group is composed of accelerator TMTM, dicumyl peroxide, and trimethylolpropane triacrylate in a weight ratio of 1.25-2.8:0.6-0.8:

1.

6. The vulcanization molding process for plastic rubber according to claim 1, characterized in that, The process parameters for step S1 are as follows: open mill roll temperature 40-44℃, roll gap 0.32-0.38mm, number of thin passes 10-14 times, each thin pass lasting 25-35s, rubber material residence time 8-12s between two adjacent thin passes, and rubber material residence time 8-12min after thin pass; the segmented heating reaction is carried out under a closed nitrogen atmosphere, with the first stage reaction temperature at 126-134℃ and reaction time at 1.8-2.2h, and the second stage reaction temperature at 92-98℃ and reaction time at 1.3-1.7h.

7. The vulcanization molding process for plastic rubber according to claim 1, characterized in that, In step S2, the chelation coating temperature is 53-57℃ and the chelation coating time is 1.3-1.7h; the heat setting coating temperature is 53℃-74℃ and the heat setting coating time is 2.8-3.2h.

8. The vulcanization molding process for plastic rubber according to claim 1, characterized in that, In step S3: the first stage internal mixing temperature is 138-145℃, the stirring speed is 220-260r / min, and the mixing time is 6-8min; the second stage internal mixing temperature is 126-134℃, the stirring speed is 200-240r / min, and the mixing time is 8-10min; during low-temperature open mill mixing, the open mill roller temperature is 48-56℃, the roller gap is 0.6-0.8mm, the main vulcanizing group is added first and mixed for 1.8-2.2min, then the interface vulcanizing group, zinc oxide, stearic acid, and antioxidant are added and mixed for 2.3-2.7min, and the sheet temperature of the mixed rubber is controlled at 65℃ or below.

9. The vulcanization molding process for plastic rubber according to claim 1, characterized in that, In step S4, after the cured rubber compound is loaded into the mold, it is first pre-pressed at 5.1-5.5MPa for 1-2 minutes, and then depressurized and vented 3-4 times, each time for 8-12 seconds. After venting, a constant pressure of 5.1-5.5MPa is maintained for gradient vulcanization. The first stage vulcanization temperature is 129-133℃ and the holding temperature is 5-7 minutes. The second stage vulcanization temperature is 142-146℃ and the holding temperature is 4-5 minutes. The third stage vulcanization temperature is 151-155℃ and the holding temperature is 2-4 minutes.

10. A plastic rubber prepared by a vulcanization molding process according to any one of claims 1-9.